(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The relevance of the subject matter is connected with the emotional burnout and its long-lasting negative consequences for both the individual and society becoming commonplace. Background: The paper covers the psychological reconstruction of the concept of "burnout" in terms of its implicit understanding and differentiated diagnosis. Method: The consolidated empirical data on the commonness of burnout among various categories of employees obtained using the MBI questionnaire. The descriptive statistics were presented for nine different professional groups (total of 441 people) of different age, degree of personal responsibility and emotional involvement in their job — the frequency analysis of expressiveness of emotional burnout syndrome performed in the context of the procedural-dynamic model. Results: Results revealed that the symptoms of burnout are quantitatively and qualitatively vary in different occupational settings. Based on the content analysis of the data obtained through face-to-face psychological counselling of clients, a list of manifestations and experiences was developed, accompanying burnout complaints as a component of a difficult life situation: emotional and motivational-semantic sphere, life position, behavioural, and psychological and physiological aspects. Conclusion: Attention was drawn to the necessity of clarification of social-psychological norms and clinical signs, which reliably and differentially diagnose its symptoms (in contrast to fatigue, depression or normative age crises). The conclusions provide suggestions and solutions on the principles of psychological prevention and assistance (self-help) in situations of emotional burnout.